A microanalysis approach to investigate problems encountered in mycology. - Thibaut, M. (1978)
X-ray microanalysis has been applied to the study of pathogenic fungi for the acquisition of chemical information. The technique of combined scanning electron microscopy and wavelength dispersive spectrometry is described. The chemical analysis depends on the characteristic x-ray spectrum excited by the electrons passing through the sample. This spectrum is analyzed by x-ray wavelength dispersion using crystal spectrometers. All the elements of the periodic system above beryllium can be detected with good sensitivity.